Current applications and future prospects of nanotechnology in cancer immunotherapy - Yan, Sen (Cancer Biol Med, 2019)
Cancer immunotherapy is an artificial stimulation of the immune system to recognize cancer cells and activate specific immune cells to target and attack cancer cells. In clinical trials, immunotherapy has recently shown impressive results in the treatment of multiple cancers. Thus, cancer immunotherapy has gained a lot of attention for its unique advantages and promising future. With extensive research on cancer immunotherapy, its safety and effectiveness has gradually been revealed. However, it is still a huge challenge to expand and drive this therapy while maintaining low toxicity, high specificity, and long-lasting efficacy. As a unique technology, nanotechnology has been applied in many fields, the advantages of which will promote the development of cancer immunotherapies. Researchers have tried to apply nanomaterials to cancer immunotherapy due to their advantageous properties, such as large specific surface areas, effective drug delivery, and controlled surface chemistry, to improve treatment efficacy. Here, we briefly introduce the current applications of nanomaterials in cancer immunotherapy, including adoptive cell therapy (ACT), therapeutic cancer vaccines, and monoclonal antibodies, and throw light on future directions of nanotechnology-based cancer immunotherapy.